Culturable diversity and antimicrobial activity of Actinobacteria from marine sediments in Valparaíso bay, Chile - Claverías, Fernanda P.; Undabarrena, Agustina N.; González, Myriam; Seeger, Michael; Cámara, Beatriz P. (Frontiers in Microbiology, 2015)
Marine-derived Actinobacteria are a source of a broad variety of secondary metabolites with diverse biological activities, such as antibiotics and antitumorals; many of which have been developed for clinical use. Rare Actinobacteria represent an untapped source of new bioactive compounds that have been scarcely recognized. In this study, rare Actinobacteria from marine sediments were isolated from the Valparaíso bay, Chile, and their potential to produce antibacterial compounds was evaluated. Different culture conditions and selective media that select the growth of Actinobacteria were used leading to the isolation of 68 bacterial strains. Comparative analysis of the 16S rRNA gene sequences led to identifying isolates that belong to the phylum Actinobacteria with genetic affiliations to 17 genera: Aeromicrobium, Agrococcus, Arthrobacter, Brachybacterium, Corynebacterium, Dietzia, Flaviflexus, Gordonia, Isoptericola, Janibacter, Microbacterium, Mycobacterium, Ornithinimicrobium, Pseudonocardia, Rhodococcus, Streptomyces, and Tessaracoccus. Also, one isolate could not be consistently classified and formed a novel phylogenetic branch related to the Nocardiopsaceae family. The antimicrobial activity of these isolates was evaluated, demonstrating the capability of specific novel isolates to inhibit the growth of Gram-positive and Gram-negative bacteria. In conclusion, this study shows a rich biodiversity of culturable Actinobacteria, associated to marine sediments from Valparaíso bay, highlighting novel rare Actinobacteria, and their potential for the production of biologically active compounds.